2017
DOI: 10.1155/2017/4851612
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Production of D(−) Lactic Acid by Sporolactobacillus nakayamae: Investigation of Fermentation Parameters and Fed-Batch Strategies

Abstract: The interest in the production of lactic acid has increased due to its wide range of applications. In the present study, the variables that affect fermentative D(−) lactic acid production were investigated: neutralizing agents, pH, temperature, inoculum percentage, agitation, and concentration of the medium components. An experimental design was applied to determine the optimal concentrations of the medium components and fermentation was studied using different feeding strategies. High production (122.41 g/L) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Figure 2c shows that the ideal concentration for greater lactic acid production was between 30 and 50 g/L of yeast extract and the ideal percentage of inoculum was between 10 and 20%. Beitel et al [19] found that maximum lactic acid production (113.73 g/L) and a low concentration of residual sucrose (3.37 g/L) were obtained when 20% (v/v) inoculum was used in the culture medium. However, a lower concentration of lactic acid was obtained (82.34 g/L) using 5% (v/v) inoculum, which may be attributed to the low density of the inoculum.…”
Section: Optimization Of L(+)lactic Acid Production Using Response Surface Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 2c shows that the ideal concentration for greater lactic acid production was between 30 and 50 g/L of yeast extract and the ideal percentage of inoculum was between 10 and 20%. Beitel et al [19] found that maximum lactic acid production (113.73 g/L) and a low concentration of residual sucrose (3.37 g/L) were obtained when 20% (v/v) inoculum was used in the culture medium. However, a lower concentration of lactic acid was obtained (82.34 g/L) using 5% (v/v) inoculum, which may be attributed to the low density of the inoculum.…”
Section: Optimization Of L(+)lactic Acid Production Using Response Surface Methodsmentioning
confidence: 99%
“…High performance liquid chromatography of the fermented broth was used for the quantification and determination of L(+)lactic acid according to Beitel et al [19], using a column Rezex ROA 300 mm × 7.8 mm (phenomenex, Burlington, MA, USA) and differential refracting index detector (Shimadzu Ultra Fast Liquid Chromatograph, Kyoto, Japan ). The mobile phase (0.005 M H 2 SO 4 ) was fed at a flow rate of 0.6 mL/min, and the temperature was kept 65 • C, and Chirex 2126 Phenomenex (150.00 × 4.60 mm) column with 1 mM of CuSO 4 as the mobile phase at 1 mL/min and temperature of 26 • C, respectively.…”
Section: Analytical Techniquesmentioning
confidence: 99%
See 3 more Smart Citations